Promotion of Project «Antiplagiat.RSL» for Raising the Level of Russian Education and Science - N. V. Avdeeva; I. V. Sus (Открытое образование (Москва))
Nowadays the plagiarism problem has become a real nuisance for the spheres of science and education, thus the specialists of the Russian State Library resolved to study the issue in depth. The results of those studies were planned to be organized in a series of articles to be published. Purpose: The article is devoted to the key aspects connected with usage of digital collection of dissertation theses and author’s abstracts together with the “Antiplagiat.RSL” software for plagiarism tests. There are given grounds for broadening the scope of verification by way of involving more educational and research organizations with their works to be studied. Materials and Methods: Using the materials of the results of the plagiarism tests carried out at the Russian State Library and having analyzed the foreign publications on the theme, the authors offer systematization of the common types of the borrowings revealed. The article points out their routes and brings forth the prognosis of the development of Russian education and science in view of plagiarism resentment with drawing the attention of the scientific community to the existing problem and supporting the atmosphere of intolerance towards the very phenomenon as such. Results: The authors bring the information concerning the development of the digital dissertation base of the RSL. There is given characteristics of the service offering the scientific and educational establishments of the nation to carry out an independent and objective examination of the texts to be published. The article would also prove the uniqueness of that kind of offer due to the opportunity to verification of the texts against the original database and to the presence of the scientifically sound methodology on which the verifications are based. Conclusions: The necessity of independent and objective evaluation of incorrect borrowings in thesis and other research papers has long ago been stated. Still there evidently lacks a somewhat common idea of who and how could realize the evaluation procedure, and on which grounds too. The Russian State Library deserves a leading position in this respect for its possessing a rich collection of research works in Russian and in foreign languages as well. Its expertise could become a part of a certain regulation mechanism for supervising norms of academic integrity.